Dukungan Keluarga dengan Kunjungan Lanjut Usia di Posyandu Lansia - Martina Ayu Pangau; Agust Arthur Laya; Bayu Dwisetyo (Inovasi Kesehatan Global, 2025)
The Elderly Posyandu plays a very important role in maintaining the health and quality of life of the elderly in the community. Family support plays a crucial role in encouraging the activity of the elderly to visit the elderly posyandu. The objective of this study is to determine the relationship between family support and elderly visits to the elderly posyandu in Environment 2, Pandu Village, Bunaken District, Manado City. The research uses a descriptive-analytical design with a cross-sectional method. The sample in this study consisted of 44 respondents using purposive sampling technique. Data collection on family support and posyandu visits was conducted using a questionnaire, and analyzed using the chi-square statistical test. The results of the study on family support showed that the most common type of family support was in the good category, with 26 respondents (59.1%), while the most frequent type of posyandu visits was in the active category, with 23 respondents (52.3%). The chi-square test result showed a p-value of 0.000, where < α 0.05. Conclusion there is The relationship between family support and elderly visits at the elderly posyandu in Environment 2, Pandu Village, Bunaken District, Manado City.